Dietary Service Staffing Impact Nutritional Quality in Nursing Homes. (May 2019) - Smith, Kelly M.; Thomas, Kali S.; Johnson, Shanthi; Meng, Hongdao; Hyer, Kathryn
Objective: To examine the relationship between dietary service staff and dietary deficiency citations in nursing homes (NHs).Method: 2007-2011 Online Survey and Certification and Reporting data for 14, 881 freestanding NHs were used to examine the relationship between dietary service staff and the probability of receiving a dietary service–related deficiency citation. An unconditional logit model with random effects was employed.Results: Findings suggest that higher staffing levels for dietitians (odds ratio [OR] = .955; p < .01), dietary service personnel (OR = .996; p < .01), and certified nursing assistants (CNAs; OR = .981; p < .05) decrease the likelihood of receiving a dietary service deficiency citation.Conclusion: Higher levels of dietary service and CNA staffing levels have the potential to improve the quality of nutritional care in NHs. Findings help substantiate the Centers for Medicare and Medicaid Services' proposed rules for more stringent Food and Nutrition Services in the NH setting and signify the need for further research relative to the impact of dietary service staff on nutritional and clinical outcomes.